In vivo and In vitro Interactions between Pseudomonas aeruginosa and Staphylococcus spp. - Hotterbeekx, An; Kumar-Singh, Samir; Goossens, Herman; Malhotra-Kumar, Surbhi (Frontiers in Cellular and Infection Microbiology, 2017)
The significance of polymicrobial infections is increasingly being recognized especially in a biofilm context wherein multiple bacterial species – including both potential pathogens and members of the commensal flora – communicate, cooperate and compete with each other. Two important bacterial pathogens that have developed a complex network of evasion, counter-inhibition and subjugation in their battle for space and nutrients are Pseudomonas aeruginosa and Staphylococcus aureus. Their strain- and environment-specific interactions, for instance in the cystic fibrosis lung or in wound infections, show severe competition that is generally linked to worse patient outcomes. For instance, the extracellular factors secreted by P. aeruginosa have been shown to subjugate S. aureus to persist as small colony variants. On the other hand, data also exist where S. aureus inhibits biofilm formation by P. aeruginosa but also protects the pathogen by inhibiting its phagocytosis. Interestingly, such interspecies interactions differ between the planktonic and biofilm phenotype, with the extracellular matrix components of the latter likely being a key, and largely underexplored, influence.This review attempts to understand the complex relationship between P. aeruginosa and Staphylococcus spp., focusing on S. aureus, that not only is interesting from the bacterial evolution point of view, but also has important consequences for our understanding of the disease pathogenesis for better patient management.